The Effect of Personal Selling, Premium Prices, and Income Levels on Interest in Buying Insurance Products in (Case Study on Millennial Generation and Gen-Z in Medan City) - Pakpahan, Belsasar; Batubara, Jastin Yehezkiel; Sembiring, Brema; Sibarani, Hendra Jonathan; Sipayung, Sari Mariahma Nova (International Journal Of Economics Social And Technology (IJEST), 2023)
One of the things that can minimize the risk to life is to have insurance because insurance provides benefits to people's lives by reducing the assets that must be set aside to cover losses from various other risks obtained. Personal selling is a benchmark for assessing the company to give customers confidence in the insurance products owned by the company. In addition, the premium price is the determination of customers purchasing insurance products with the level of income as an assessment of the customer's ability to have protection from the risks of life. This research uses a quantitative approach with a sample of 100 respondents. Data analysis in this study used SmartPLS 4.0. Hypothesis testing with the PLS approach is carried out in two stages, namely testing the outer model and the inner model. The results showed that personal selling has a positive and significant effect on purchase intention, the premium price has no significant effect on purchase intention, income level has a negative and significant effect on purchase intention, and personal selling, premium price, and income level simultaneously have a positive and significant effect on purchase intention in Millennial Generation and Gen-Z in Medan City